Synesthesia in Contemporary Music: Relationship between Sound and Color in a Musical Composition - Rivera Fernández, María Luz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this work we present the complex relationship between sound and color in musical creation throughout history that continues to be fruitful in current musical composition. Synesthesia in music establishes a correspondence between sound and color and has been a constant debate since the 17th century. The complex nature of sound appears from ancient Greece in the school of Pythagoras in which the number becomes the configurator of harmony. Since then, different aesthetic attempts have arisen to relate color and sound that reach today's electronic procedures in contemporary music.